Basic biochemical and hematological parameters of structural hemoglobin variants in the postpartum women and their respective newborn from Manaus, Amazonas, Brazil - Roberta da Silva Brito; Lecita Marreira de Lima Barros; Lilian Wallace Moreira; Regina Neves Normando; Thiago Bacha de Jesus; Marilda de Souza Gonçalves; Rajendranath Ramasawmy; Stéfani Ferreira de Oliveira; Keyla Emanulle Ramos da Silva; Nelson Abrahim Fraiji; Larissa Feitosa da Hora; Rebeca Linhares de Abreu Netto; et al. (BMC, 2022)
Abstract The present study aimed at estimating the prevalence of structural hemoglobinopathies in newborn and describing the hematological and biochemical characteristics between postpartum women (PW) and their respective newborns (NB) at a public maternity hospital in Manaus, Amazonas state, Brazil. In total, 825 NB and 820 PW were included in the study. Hematological and biochemical analysis and screening of structural hemoglobinopathies were performed and compared in groups of individuals (NICU or not; hemoglobin genotypes; gestational age and prenatal). The age of PW ranged from 13 to 44 years old (mean of 23.7 ± 6.6 years), with 45.9% pregnant for the first time and 54.1% multiparous. Reported receiving prenatal care 88% and regarding the type of delivery, 47.7% had delivered by cesarean section. Among the births, 19.4% were born premature and 8.3% were admission to the neonatal intensive care unit (NICU). The male NB represented 53.4% of the total. Sickle cell trait (FAS) was found in 16 (1.94%) and heterozygous for D hemoglobin (FAD) in 6 (0.73%) newborns. A statistically significant values was found between the previous history of miscarriage and increase of Mean corpuscular volume (MCV) (p < .001), Red blood cell distribution width (RDW) (p = .003), total and indirect bilirubin concentration (p < .001) and LDL cholesterol (p = .004). Hemoglobin levels below 13.5 g/dL was found in 66% black newborns, compared with 15% of Afro-Brazilian and 5% of whites. The frequency of structural hemoglobinopathies was higher in African-Brazilian newborn babies (78%) and those who with low birth weight had a higher frequency of NICU (35.7%). Interestingly, underage mothers had a higher frequency of NB with low birth weight and premature birth. Postpartum women who had children carriers of FAS and FAD had a higher frequency of urinary tract infection (65.2%) and moderate anemia (23.8%). This study estimated for the first time the prevalence of structural hemoglobinopathies in NB in Manaus, Amazonas, Brazil. Despite the small prevalence of, we highlight the importance of early diagnosis of hemoglobin variants, contributing to the improvement of the quality of life of PW and your NB, reinforce the need to implement educational and prevention programs to raise awareness among the population and in order to counsel parents regarding the probability of having a child with abnormal hemoglobins homozygous as HbSS or HbCC.